Aksjologia literacka w pismach Jerzego Stempowskiego - Kudyba, Wojciech (Colloquia Litteraria, 2013)
For Stempowski the act of reading is inevitably linked to assessment and valuation. In his writings the poetics of reading takes shape of a specific axiology of reception. It becomes the theory of worthful reading. Looking from a perspective of an amateur reader allowed for the essayist to recognize the fragile bases of literary criticism, the dogmatism of a theoretic approach, and finally, the literary historians’ insensitivity to the contextual and situational values of the analysed works. It is precisely this attachment to the amateurish, i.e. affective and ‘loving’, relation with a piece of written work that prompted Stempowski to search for a look at literature that would not kill the joy of reading; one that would not limit the cognitive horizons and would also take into account the contextuality of literary works and their inevitable relation with the extra-literary reality that the reader is plunged into.